La morte e la storia (Altre Modernità, 2020)
This work compares two profiles of artists, similar in many respects, who have crossed paths without knowing each other and whose early death has reshuffledthe meaning of their art. For both, the body has been a central theme of artistic production, and in the case of both, it was the body that betrayed and abandoned them precociously, apparently interrupting an incomplete artistic parable, actually recalibrating it in the light of the end of life. Through the confrontation between Derek Jarman and Pier Paolo Pasolini, the question of art as a sense of existence and a summary of one’s role in the world is addressed.
Keywords: Pier Paolo Pasolini; Derek Jarman; Death; art; will